Evaluation for shunted pouches of cavernous sinus dural arteriovenous fistula and the treatment outcome of transvenous embolization. Issue 2 (April 2018) - Sato, Masaki; Izumi, Takashi; Matsubara, Noriaki; Nishihori, Masahiro; Miyachi, Shigeru; Wakabayashi, Toshihiko
Background: This study aimed to evaluate the detailed location and the number (single or multiple) of cavernous sinus dural arteriovenous fistula (CSDAVF) shunted pouches as well as the relationship between the characteristics of shunted pouch(es) and the treatment outcome of transvenous embolization for CSDAVF. Methods: A total of 23 consecutive patients with CSDAVFs who underwent angiogram and transvenous embolization were retrospectively analyzed. Shunted pouches were assessed using three-dimensional angiogram and multiplanar reformatted image obtained from the rotational angiogram data. Results: Of the 23 patients with CSDAVFs, 40 shunted pouches were identified. Twelve CSDAVFs had a single shunted pouch, and 11 had multiple shunted pouches. The mean CSDAVF with multiple shunted pouches was 2.5. The shunted pouches were more often found in the posterior compartment of the CS, which was connected with the intercavernous sinus (23/40; 57.5%). In 12 CSDAVFs with a single shunted pouch, 10 were treated with selective embolization and complete occlusion was achieved during the follow-up. Two CSDAVFs with single shunted pouch were just observed without intervention, and DAVFs disappeared spontaneously during the follow-up period. In 11 CSDAVFs with multiple shunted pouches, eight were treated with selective embolization and three with sinus embolization. In six of eight (75%), complete occlusion was achieved following selective embolization, but two of eight (25%) recurred and required retreatment. Conclusions: Rotational angiography data suggested that the shunted pouches of CSDAVFs were mostly located in the posterior compartment of the CS connected with the intercavernous sinus. Selective embolization for CSDAVFs with a single shunted pouch is the first-line treatment alternative to sinus packing, and selective embolization with multiple shunted pouches will be a considerable treatment option.